2009
DOI: 10.1111/j.1365-2133.2009.09326.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of matrix metalloproteinases in photodamaged skin by photodynamic therapy

Abstract: Skin remodelling induced by MAL-PDT was demonstrated in photodamaged skin. Two sessions of MAL-PDT increases immunohistochemical expression of MMP-9 in the dermis at 3 months after treatment, and also of collagen type I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 11 publications
5
31
0
Order By: Relevance
“…The proliferation of osteoblasts26 and alveolar bone cells27 treated with 1~5% PRP was higher than that of cells treated with higher concentrations of PRP. Similarly, it was shown that maximal stimulation of HDF proliferation was achieved using 5% aPRP29. Our study indicates that aPRP stimulates the proliferation of HDF, consistent with the findings described above.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The proliferation of osteoblasts26 and alveolar bone cells27 treated with 1~5% PRP was higher than that of cells treated with higher concentrations of PRP. Similarly, it was shown that maximal stimulation of HDF proliferation was achieved using 5% aPRP29. Our study indicates that aPRP stimulates the proliferation of HDF, consistent with the findings described above.…”
Section: Discussionsupporting
confidence: 92%
“…This stimulation of de novo collagen synthesis may compensate for the defects that arise due to the fragmentation or loss of collagen in photoaged and aged skin. Accumulation of this newly-synthesized collagen may improve the structural integrity of the dermal ECM and stimulate fibroblasts to produce more collagen29.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher success rates for fine lines and coarse wrinkles at the final visit on the ALA‐IPL PDT side were also found. Improvement in fine lines and wrinkles on the ALA‐IPL PDT side was seen even after the treatment was finished, as has been reported previously 10 . This, as suggested in our case, was due to subjects not strictly avoiding the sun, in which cases, sunlight served as a huge low‐dose activator of the remaining PpIX.…”
Section: Discussionsupporting
confidence: 86%
“…The accumulation of partially degraded and fragmented collagen, such as it is present in photoaged skin, inhibits neocollagenesis 22 . Proteolytic clearance of fragmented collagen by MMPs plays therefore a decisive role in restoring collagen biosynthesis, 23,24 whereas induction of MMPs by non‐ablative laser energy and PDT is quantitatively more modest than with CO 2 ‐laser 14,22,25,26 …”
Section: Discussionmentioning
confidence: 99%